Selective Blockade of Tumor Necrosis Factor Receptor I Inhibits Proinflammatory Cytokine and Chemokine Production in Human Rheumatoid Arthritis Synovial Membrane Cell Cultures. Issue 9 (26th August 2013) - Schmidt, Emily M.; Davies, Marie; Mistry, Prafull; Green, Patricia; Giddins, Grey; Feldmann, Marc; Stoop, A. Allart; Brennan, Fionula M.
<x xml:space="preserve">Abstract</x> Objective To determine whether selective blockade of tumor necrosis factor receptor I (TNFRI) affects spontaneous proinflammatory cytokine and chemokine production in ex vivo–cultured human rheumatoid arthritis synovial membrane mononuclear cells (MNCs) and to compare this response to that of TNF ligand blockade using etanercept. Methods A bispecific, single variable‐domain antibody (anti‐TNFRI moiety plus an albumin binding moiety [TNFRI‐AlbudAb]) was used to selectively block TNFRI. Inhibition of TNFα‐mediated responses in cell lines expressing TNFRI/II confirmed TNFRI‐AlbudAb potency, human rhabdomyosarcoma cell line KYM‐1D4 cytotoxicity, and human umbilical vein endothelial cell (HUVEC) vascular cell adhesion molecule 1 (VCAM‐1) upregulation. Eighteen RA synovial membrane MNC suspensions were cultured for 2 days or 5 days, either alone or in the presence of TNFRI‐AlbudAb, control‐AlbudAb, or etanercept. Proinflammatory cytokines and chemokines in culture supernatants were measured by enzyme‐linked immunosorbent assays. A mixed‐effects statistical analysis model was used to assess the extent of TNFRI selective blockade, where the results were expressed as the percentage change with 95% confidence intervals (95% CIs). Results TNFRI‐AlbudAb inhibited TNFα‐induced KYM‐1D4 cell cytotoxicity (50% inhibition concentration [IC50] 4 nM) and HUVEC VCAM‐1 up‐regulation (IC50 12 nM) in a dose‐dependent manner. In ex vivo–cultured RA synovial membrane MNCs, selective blockade of TNFRI inhibited the production of proinflammatory cytokines and chemokines to levels similar to those obtained with TNF ligand blockade, without inducing cellular toxicity. Changes in cytokine levels were as follows: −23.5% (95% CI −12.4, −33.2 [P = 0.004]) for granulocyte–macrophage colony‐stimulating factor, –33.4% (95% CI –20.6, –44.2 [P ≤ 0.0001]) for interleukin‐10 (IL‐10), –17.6% (95% CI 3.2, –34.2 [P = 0.0880]) for IL‐1β, and –19.0% (95% CI –3.4, –32.1 [P = 0.0207]) for IL‐6. Changes in chemokine levels were as follows: –34.2% (–14.4, –49.4 [P = 0.0030]) for IL‐8, –56.6% (–30.7, –72.9 [P = 0.0011]) for RANTES, and –24.9% (2, –44.8 [P = 0.0656]) for monocyte chemotactic protein 1. Conclusion In ex vivo–cultured RA synovial membrane MNCs, although a limited role of TNFRII cannot be ruled out, TNFRI signaling was found to be the dominant pathway leading to proinflammatory cytokine and chemokine production. Thus, selective blockade of TNFRI could potentially be therapeutically beneficial over TNF ligand blockade by retaining the beneficial TNFRII signaling.